System Authentication System - Syed Mahboob, Syed Suwaid Ullah Hussaini, Mohammed Rahmat Ali (Mathematical Statistician and Engineering Applications, 2023)
A graphical password secure authentication system is one of technic for authentication of computer security. Today, computer science’s most crucial component for protecting user or client data is digital/computer security. And one of the hazards is shoulder-surfing, in which a thief might obtain a password by keeping watch on the authentication process or filming it. There are several approaches for this authentication, with the Graphical Password Technique being the most popular and straightforward. So, we provide a fresh approach to solve this issue. To defend against shoulder surfing attacks, we have created two ideas. To start, the user must create one if there is no registration. Second, you need to sign in using a legitimate user ID and password. It is the password an assortment of letters and digits. Third, the user must pass an image-based authentication process where they can select the likelihood of a password and this strategy working against one other is greater. You should select a password based on your registration. password must match when logging in. You need to upload an image of your choice, then the image is divided into four parts. Multiple images should be selected in graphical password authentication, and You must remember the password sequence. Like three-factor authentication, too. So, this is proposed a new graphical password secure authentication system that is resistant to shoulder surfing as well as other forms of attacks and probable assaults.